PENERAPAN PAKAN SUPLEMEN BLOK UKKMB DAN JERAMI FERMENTASI PADA PKM KELOMPOK TANI TERNAK SAPI BALI DI DESA LEMPANG KECAMATAN TANETE RIAJA KABUPATEN BARRU - Effendi Abustam; Muhammad Yusuf; Muhammad Irfan Said (Universitas Airlangga, 2019)
PKM Livestock Farmers Group in Lempang Village Barru District has been conducted on two partnersnamely Sikapa Livestock Group and Livestock Group Padaelo in Tanete Riaja District which lasts from July to September 2018. The technology applied by the team is the manufacture of UKKMB blocks feed supplement and probiotic fermentation straw on. This activity aims to improve the skills of members of livestock groups in the application of livestock technology, especially in the manufacture of feed. The productivity of Bali cattle needs to be improved through the provision of quality feed as one of the problems found. The implementation method is in the form of training (theory and practicum), action review, mentoring and application of feed products to Bali cattle in a cage. Making modified feed supplements in the form of UMMB into Urea Water Collagen Coconut Multinutrient Block (UKKMB) and probiotic fermented rice straw is the main product tried in Bali cattle at home. The provision of block supplement feed in Bali cattle increases appetite and feed consumption. The results of the activity showed that UKKMB and probiotic fermented rice straw could solve the problem of the availability of feed in the cage and the increase in cattle weight.